On the presence of the poorly documented Hypostomus isbrueckeri Reis, Weber & Malabarba, 1990 (Siluriformes: Loricariidae) in Argentina and extension of its distribution range - Teran, Guillermo Enrique (2022)
Hypostomus Lacépède is the most speciose loricariid genus, including about 150 valid species (Fricke et al. 2022). It has a wide distribution in the Neotropical basins, occurring from Central America to the Salado River, South of the La Plata River in the Province of Buenos Aires, Argentina (Ringuelet 1975; López 1992; Fricke et al. 2022). In Argentina the genus was recorded for the first time in 1876 (Weyenbergh 1876; Koerber & Weber 2014), and there are currently 26 species considered as present or probably present in the country (Cardoso et al. 2011, 2012, 2016, 2019; Koerber & Weber 2014; Terán et al. 2020). Some of these species are poorly documented in the literature since the records lack traceable voucher specimens, detailed descriptions and photographs, necessary conditions to make reliable and falsifiable faunal records (Serra et al. 2021). In recent collection campaigns in the Uruguay river basin in the province of Corrientes (Argentina), we collected specimens of Hypostomus that were identified by comparison with collection specimens and literature information.